Community pharmacists' awareness toward their roles in healthcare and interaction with general practitioners: A cross-sectional study - Alamin Hassan Mohamed Alamin Alabid; Mohamed Izham Mohamed Ibrahim; Mohamed Azmi Hassali; Subish Palaian (Wolters Kluwer Medknow Publications, 2021)
Introduction: There is a paucity of data on the extended role of community pharmacists (CP) in Malaysia. This study is aimed to evaluate CPs awareness toward their roles in healthcare and interaction with general practitioners (GPs). Materials and Methods: A cross-sectional design using a validated questionnaire was conducted nationwide among randomly selected Malaysian CPs. The questionnaire consisted of consisted of 32 questions with three sections. The Cronbach's alpha measure for the scale on awareness was 0.494 and 0.724 for the interaction between CPs and GPs. Descriptive statistics were reported. The Chi-square test, Mann-Whitney test, Kruskal-Wallis test, and post hoc analyses were applied at the alpha level of 0.05. Results: Of the 127 CPs who filled out the responses, 57.5% (n = 73) mentioned that they rarely or never interacted with GPs. Many CPs (n = 106, 83.5%) were aware of their role in providing patient education, and 109 (85.8%) indicated that they could suggest nonprescription medicines to patients, whereas 88 respondents (69.3%) were aware that they could suggest alternative medicines. A total of 117 respondents (92.1%) indicated their willingness to perform selected screening tests and identify and prevent prescription errors. A considerable number of CPs (n = 76, 59.8%) were aware of their ability to design and regulate prescribed regimens, and 89 (70.1%) showed their willingness to monitor these regimens. The total average score of the CPs' awareness toward their roles in providing healthcare for the 16 activities/items and the value of the interaction mean score was 12.00 (±2.92), with a median score of 12.00 (interquartile range: 9.5-14.5). Conclusions: Malaysian CPs are fully aware of their role in providing healthcare and pharmaceutical care. Though the majority of them were willing to provide extended services, they are often unable to perform these roles due to the lack of interprofessional collaboration, lack of time, and absence of remuneration for their extended services. Training programs, practice guidelines, and professional service fee may encourage CPs to perform more extended services.